The optimistic utopia: sacrifice and expectations of political transformation in the Angolan Revolutionary Movement - Blanes, Ruy Llera (Social Anthropology, 2021)
In this paper, I propose an anthropological discussion of the correlation of utopia and optimism, in relation with ideas of personal and collective sacrifice. To do so, I will invoke my ethnographic research on political activism in Angola, particularly the so‐called Revolutionary Movement – a group of young activists challenging Angola’s authoritarian regime. During recent Luanda fieldwork, I observed how most of the ‘Revús’engaged in self‐sacrificial behaviour, exposing themselves to police brutality, imprisonment and social discrimination, in their struggle towards a brighter collective future. This optimistic and somewhat Gandhian stance marks a dramatic departure from the sense of fatalism and ‘culture of fear’ that seems otherwise to prevail in Angola. I will question if and in what terms such stances are ‘utopian’ and configure ‘principles of hope’, as Ernst Bloch would put it. In the process, I will perform a critical interrogation of the correlation of utopia, hope and optimism